Structure and function of the juxtamembrane GAF domain of potassium biosensor KdpD. (17th August 2020) - Kumar, Shivesh; Gillilan, Richard E.; Yernool, Dinesh A.
Abstract: KdpD/KdpE two‐component signaling system regulates expression of a high affinity potassium transporter responsible for potassium homeostasis. The C‐terminal module of KdpD consists of a GAF domain linked to a histidine kinase domain. Whereas certain GAF domains act as regulators by binding cyclic nucleotides, the role of the juxtamembrane GAF domain in KdpD is unknown. We report the high‐resolution crystal structure of KdpD GAF domain (KdpD G ) consisting of five α‐helices, four β‐sheets and two large loops. KdpD G forms a symmetry‐related dimer, wherein parallelly arranged monomers contribute to a four‐helix bundle at the dimer‐interface, SAXS analysis of KdpD C‐terminal module reveals an elongated structure that is a dimer in solution. Substitution of conserved residues with various residues that disrupt the dimer interface produce a range of effects on gene expression demonstrating the importance of the interface in inactive to active transitions during signaling. Comparison of ligand binding site of the classic cyclic nucleotide‐binding GAF domains to KdpD G reveals structural differences arising from naturally occurring substitutions in primary sequence of KdpD G that modifies the canonical NKFDE sequence motif required for cyclic nucleotide binding. Together these results suggest a structural role for KdpD G in dimerization and transmission of signal to the kinase domain.